Pretty Good for a Girl : Women in Bluegrass - Henry, Murphy (Book collections on Project MUSE., 2013)
This book documents the lives of more than seventy women whose vibrant contributions to the development of bluegrass have been, for the most part, overlooked. Organized by decade, the book begins with Sally Ann Forrester, who played accordion and sang with Bill Monroe's Blue Grass Boys from 1943 to 1946, and continues into the twenty-first century with artists such as Alison Krauss, Rhonda Vincent, and the Dixie Chicks.